Vous êtes sur la page 1sur 9

Collection of Solved Problems in Physics

The motion of a charged particle in homogeneous perpendicular electric and


magnetic elds
Task number:402

A particle with a positive charge Q begins at rest. Describe the motion of the particle after switching
on both a homogeneous electric eld with direction corresponding to the z axis and a homogeneous
magnetic eld with direction corresponding to the x axis.

Hint

There is a Lorentz force acting on a charged particle in an electromagnetic eld. This force causes the
particles movement. We should determine the particles trajectory, then nd out an equation for the
particles motion and solve it.
Analysis

A particle is placed in an electromagnetic eld which is characterized by two vectors perpendicular to


each other: electric eld E and magnetic eld B. Both the electric and magnetic elds act on the
particle with forces. The force of the electrical eld is parallel to the electric eld vector and also to the
z axis. The magnetic force is perpendicular to the magnetic eld vector which is parallel to the x axis.
The net force of both the electric and magnetic forces acts in the yz plane. Because the particles initial
velocity is zero, its motion will be in the yz plane.
Lets nd an equation for the charged particles motion and solve it.
Solution

There is no force acting on the particle in the direction of the x axis. The electrical force acts in the
direction of the electric eld, in our case it is the direction of the z axis. The magnetic force is
perpendicular to the magnetic eld which has the same direction as the x axis, so the magnetic force
acts in the yz plane. Because the particles initial velocity is zero, its motion will be in the yz plane.
Lets mark the particles position as:
= (0, y(t), z(t))
r (t)

We get the particles velocity by taking the time derivative of its position:

= (0, vy (t), vz (t)) = (0, y(t), z(t))


v(t)

The expression for the Lorentz force acting on a charged particle in an electromagnetic eld is:
F = Q (E + v B)

The force F could be also (according to Newtons second law) expressed as the product of a particles
mass and its acceleration:
F = ma = mv

The equation of motion could now be rewritten as


mv= Q(E+ v B)

Lets rewrite the electric eld and magnetic eld in terms of components:
E= (0, 0, E)

B = (B, 0, 0)

Lets nd the vector product:


v B = (0, y, z) (B, 0, 0) = (0, Bz, By)

So, the equation of motion could be solved in three components as:


mvx = 0
mvy = 0 + QBvz
mvz = QE QBvy

There is no force acting in the direction of the x axis and thus the particles velocity in the x direction
is a constant (this ensues from the rst equation). But we know that the constant must be zero, since
the particle begins at rest. So as we assumed the motion will be only in the yz plane.
The second and third equation could resolved as
QB
vz
m

(1)

QE
QB

vy
m
m

(2)

vy =
vz =

We have obtained a system of two dierential equations.


Lets express the velocity vz from equation (1)
vz =

m
vy
QB

vz =

m
vy
QB

dierentiate it with respect to time

and insert it into equation (2):


QE
QB
m
vy =

vy
m
m
QB

Multiplying both sides of the equation by the fraction


vy + (

QB
m ,

we get:

QB 2
Q 2
) vy = ( ) EB
m
m

We have now a non-homogeneous linear dierential equation with constant coeicients. Its further
solution can be found in the following section.
Solution of the differential equation

The equation
vy + (

QB 2
Q 2
) vy = ( ) EB
m
m

(1)

is a non-homogeneous linear dierential equation with constant coeicients. Its solution has several
steps.
First we have to solve the corresponding homogeneous equation, i.e. the equation with zero on its right
side. Then we should nd a particular solution, which is a random solution of the non-homogeneous
equation. The general solution of a non-homogeneous equation is the sum of its particular solution and
the general solution of the corresponding homogeneous equation. Constants in the general solution will
be found from the initial conditions.
a) Solution of the homogeneous dierential equation
vh + (

QB 2
) vh = 0
m

The solution has to be in the following form:


vh (t) = et
vh (t) = 2 et

After substitution and some adjustment we get a new form of the equation
2 et + (
2 + (

QB 2 t
) e =0
m
QB 2
) =0
m

which is a quadratic equation for an unknown . Its solutions are


2 = (

QB 2
)
m

= i (

To make it clearer lets denote the fraction

QB
m

QB
)
m

as
=

QB
m

The homogeneous equation then has two independent solutions

vh1 (t) = eit


vh2 (t) = eit

A general solution is their linear combination


vh (t) = Aeit + Beit

(2)

Lets rewrite these complex exponentials using trigonometric functions


eit = cos(t) + i sin(t)
eit = cos(t) i sin(t)

and insert into equation (2).


vh (t) = A[cos(t) + i sin(t)] + B[cos(t) i sin(t)]

After some rearranging we get


vh (t) = (A + B)cos(t) + i(A B) sin(t)

Lets mark the sum and the dierence of constants A and B as two new constants C and D.
vh (t) = C cos(t) + D sin(t)

We have now got a general solution of the homogeneous equation, where C and D are real constants
(because we are looking only for real solutions of the given dierential equation).
b) Particular solution
The particular solution is one random solution of a non-homogenous dierential equation, i.e. an
equation with nonzero right side. There are various sorts of methods to do this, but in simple cases we
can try to guess the solution. Actually, this often works very well.
In our case equation (1) has on its right side a constant. Lets see if a particular solution of the
non-homogenous equation vp could be a constant function.
vp = konst

Derivations of such a particular solution are


vp = 0
vp = 0

Lets insert those expressions into equation (1)


vp + (
0+(

QB 2
Q 2
) vp = ( ) EB
m
m

QB 2
Q 2
) vp = ( ) EB
m
m

Then express vp
vp B = E

vp =

E
B

A particular solution has been found. It is the constant vp =

E
B

c) Complete solution of the non-homogeneous dierential equation


We will get a general solution of a non-homogenous equation from the sum of its particular solution and
the general solution of the relevant homogeneous equation, so
vy = vh + vp
vy (t) = C cos(t) + D sin(t) +

E
B

(3)

d) Determination of the constants C and D


The constants C and D can be determined from initial conditions. At the beginning (time t = 0 s) the
particle was at rest so
vy (0) = 0
vy (0) = C cos0 + D sin0 +
C+

E
=0
B

E
=0
B

We get the magnitude of the constant C


C=

E
B

To determine the second constant D lets nd the component of the velocity vz. This component can be
expressed as
vz =

m
vy
QB

The acceleration vy is determined by time dierentiation of the expression for the velocity vy.
vy (t) = C cos(t) + D sin(t) +

E
B

vy (t) = C sin(t) + D cos(t)

The component of velocity vz is


vz (t) =

m
(C sin(t) + D cos(t))
QB

From the initial conditions vz(0) = 0 we may get the constant D


vz (0) =

m
D=0
QB

D=0

Insert the determined constants C and D into the general solution (3)

(4)

vy (t) = C cos(t) + D sin(t) +

E
E
E
= cos(t) +
B
B
B

The component of velocity vy in the direction of the y axis is


E
(1 cos(t)).
B

vy (t) =

The component of velocity vz we may determine from equation (4) by inserting constants C and D
vz (t) =

m
(C sin(t) + D cos(t))
QB

vz (t) =

m E
( sin(t)) .
QB B

Be aware that
=

QB
,
m

and then for the z component of velocity we get


vz (t) =

E
sin(t).
B

Solution - looking for a trajectory

By solution of the dierential equation we have got the component of velocity vy


vy (t) =

E
(1 cos(t))
B

And the component of velocity vz


vz (t) =

where =

E
sin(t),
B

QB
m

The components of position y and z we obtain by integration over time of the respective components of
velocity.
y = vy dt =
y=

E
(1 cos(t)) dt
B

E
(t sin(t)) + y0
B

The component z can be determined by


z = vz dt =
z=

E
sin(t) dt
B

E
cos(t) + z0
B

The trajectory of a charged particle in a homogeneous electromagnetic eld is thus described by the
following equations
x=0

y=

E
(t sin(t))
B
z=

, where =

E
cos(t)
B

QB
m

The shape of the trajectory

The equations describing the trajectory of a particle in a homogeneous electromagnetic eld are
x=0
y=
z=

E
(t sin(t))
B

E
cos(t),
B

QB
m

The motion of the trajectory is composed of two independent motions one is circular motion in the
E
plane yz with radius B
and the other is uniform motion in the y. Combining those motions leads to
motion on a cycloid (a cycloid curve).
x=0
y = a(T sinT)
z = a(1 cosT)

where a is the radius of the circle and T is the angle made by the rolling of the circle (see below).

Remark: The motion of a particle in a uniform electromagnetic eld could be compared to the motion
of the tire valve of a moving wheel. Both of these motions have a cycloid trajectory.
Answer

After switching on both an electric eld in the z direction and a homogeneous magnetic eld in the x
direction, the charged particle will move on a cycloid given by the equations
x=0
y=
z=

E
(t sin(t))
B

E
cos(t),
B

QB
m

Updated: Feb. 3rd, 2016